Modern aspects and features of foreign economic activity of Ukrainian enterprises in wartime conditions - Kulish, Damir (Management and Entrepreneurship: Trends of Development, 2023)
Russia’s aggression against Ukraine mainly affects Ukraine’s production and export capabilities. The current war raises concerns about whether the harvest will be harvested. In addition, the war led to the closure of ports and oilseed crushing operations, which affected exports. Ukrainian farmers show high resistance to the hardships caused by the war, and continue to grow crop production and livestock products when the safety of agricultural land allows it. The purpose of the study is modern aspects and features of foreign economic activity of Ukrainian enterprises in wartime conditions. It is determined that since more than half of crop production in Ukraine is exported, logistics of the export supply chain plays a vital role. Before Russia’s aggression, more than 90% of Ukrainian crop exports went through the ports of the Azov and Black Seas. These ports are currently unavailable due to the ongoing war or Russian occupation. Other export channels – road, rail, and river ports – are not capable of handling the same volumes as seaports. Thus, industry estimates show that current exports account for only about 20% of normal exports. At the national and global levels, efforts are being made to increase the capacity of alternative export channels and find other outlets. However, the larger-than-usual volumes that remain in storage and the upcoming harvest in June-September 2022 will lead to rapid production of large volumes that will also need to be stored to avoid significant losses. In addition, some storage and processing facilities were damaged, which further delays and restricts the export of agricultural products from Ukraine. A full-scale invasion affects not only Ukraine’s GDP, but also its partner countries. Other countries are not yet fully aware, but if a full-scale invasion continues, the population of partner countries will feel it due to a reduction in GDP per capita. However, Ukraine will need further financial support both in the short term, as the war continues, and in the long term for recovery. And Ukrainian enterprises engaged in foreign economic activity need to develop and implement an adaptive strategy of foreign economic activity in wartime conditions. JEL Classification: N70, F1